Advanteges in RT-PCR method application to assess intestinal barrier function in broiler chickens - Shatalov, S.; Шаталов, Сергій Анатолійович; Nedzvetsky, Victor S.; Nedzvetsky, V. S.; Nedzvetsky, Viktor; Nedzvetsky, Victor; Nezdvetsky, V.; Недзвецький, Віктор Станіславович; Baydas, G.; Байдас, Г.; Baselga, R.; Баселга, Р.; et al. (Дніпровський ДАЕУ, 2023)
The application of the RT-PCR method for evaluating the intestinal barrier function in broiler chickens is an effective approach that provides precise and clear information in respect with the intestine health characteristics of the commercial animals. Застосування методу RT-PCR для оцінки бар’єрної функції кишківника у курчат-бройлерів є ефективним підходом, який надає точну та чітку інформацію щодо характеристик здоров’я кишечника промислових тварин.
Переваги застосування методу RT-PCR для оцінки бар’єрної функції кишківника у курчат-бройлерів
Недзвецький Віктор Станіславович https://orcid.org/0000-0001-8975-6952
Keywords: intestinal system; інтестинальна система; barrier function; бар’єрна функція; chickens; курчата; PCR; ПЛР